Relationship Marketing on Loyal Customer - Rizki Jaya Putra; Elke Alexandrina (Ultimacomm: Jurnal Ilmu Komunikasi, 2019)
Total Bangun Persada (TOTAL) is a construction company that builds international-standard buildings and focuses on high-end market segmentation. It has Customer Care Department which maintains relationships by answering customers’ inquiries. TOTAL’s Customer Care - after sales service takes place after the project maintenance period, to support TOTAL’s core service: “building construction”. TOTAL delivers quality service through its Customer Care as part of their relationship marketing strategy. The research is meant to discover how TOTAL’s Customer Care contributes to the relationship marketing strategy. Data analysis of the study would describes the ‘relationship marketing’ on customer market as conducted by Customer Care and to define the obstacles of the communication process in Customer Care activity. The research methodology used is qualitative to describe the communication process of relationship marketing implementation in TOTAL’s Customer Care. Serving a segmented market, TOTAL has ‘differentiation focus’ competitive advantage through lifetime guarantee in after sales service. TOTAL’s relationship marketing on customer market defined by their after sales service, does not limited to serve building repairs – compensation for damages besides civil work might occur if the cause was within TOTAL’s scope of work. With no significant communication obstacles apparent, TOTAL provides multi-channel integration for their customers such as Email for communicating detailed information; Whatsapp contact for short message or call for immediate response; office landline contact also available. External informant has positive response about TOTAL’s after sales service responsiveness provided by Customer Care Department.